(untitled) (Research, Society and Development, 2025)
The oncologic treatment causes adverse effects on patients, including oral changes, which negatively impact the qualit of life. Other factors that affect the oral condition of individuals are sociodemographic conditions and late referral for dental treatment. Objective: To identify the sociodemographic profile and to evaluate the selfperception of oral health of cancer patients treated at a dental school clinic. Method: This is a cross-sectional study with descriptive analysis, carried out through the application of na oral health perception questionnaire, followed by na intraoral clinical examination. The population was composed of cancer patients referred to initiate the dental treatment between May and July 2023. Absolute and percentage frequencies were calculated for the descriptive categorical variables. The Fisher’s Exact test was used to evaluate the association between two categorical variables, considering 5% of significance level. Results: Data from 36 participants were recorded. Males had a higher prevalence (58.3%); 61% were over 61 years old, 27.8% were illiterate and 64.9% had a family income between R 1,000.00 and R 3,000.00. Only 11.1% responded that they would look for a dentist if they felt any discomfort in their mouth, highlighting the lack of information regarding the need for dental follow-up since the initial diagnosis. Conclusion: Even in the face of oral changes resulting from antineoplastic therapy, many patients still do not have a self-perception of oral health and the importance of being monitored by a dental surgeon.